2004
DOI: 10.1152/ajpheart.00171.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-α-induced hypertrophy of neonatal rat ventricular myocytes

Abstract: . Protein kinase C-␣-induced hypertrophy of neonatal rat ventricular myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
(59 reference statements)
5
38
0
Order By: Relevance
“…In addition, PKCα regulates the hypertrophic growth of cardiomyocytes through ERK1/2 [18]. Consistent with the results of previous studies [11,24], we also found that the overexpression of either myocardin or PKCα increased the cell surface area and induced cardiac hypertrophy. Furthermore, we examined the relationship between two transcription factors, myocardin and PKCα, in the regulation of cardiomyocyte hypertrophy.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, PKCα regulates the hypertrophic growth of cardiomyocytes through ERK1/2 [18]. Consistent with the results of previous studies [11,24], we also found that the overexpression of either myocardin or PKCα increased the cell surface area and induced cardiac hypertrophy. Furthermore, we examined the relationship between two transcription factors, myocardin and PKCα, in the regulation of cardiomyocyte hypertrophy.…”
Section: Discussionsupporting
confidence: 92%
“…PMA Induces GRK5 Protein Levels and Increases Binding Activity of NF-B to the GRK5 Promoter in Myocytes-PMA is a specific activator of PKC (23), which can activate NF-B through PKC as well as through the induced formation of reactive oxygen species (ROS) (24). PMA is a well established hypertrophic agent in myocytes and, accordingly, was tested to determine whether it could induce GRK5 expression in NRVMs.…”
Section: Nf-b Proteins P50 and P65 Interact With The Promotermentioning
confidence: 99%
“…The conventional PKC isozymes, comprising, ␣, ␤I, ␤II, and ␥, are activated by Ca 2ϩ , phosphatidylserine, diacylglycerol, or phorbol esters; the novel PKC isozymes, consisting of PKC␦, -⑀, -, -, and -, are activated by phosphatidylserine, diacylglycerol, or phorbol esters, but insensitive to Ca 2ϩ ; and the atypical isoforms ( and /) are dependent on phosphatidylserine for activation, but not affected by Ca 2ϩ , diacylglycerol, or phorbol esters (1-3). Activated PKC translocates from cytosol to membranous organelles and/or to the nucleus (4,5). In addition, oxidative stress has been reported to induce prolonged activation of PKC within the cells (6 -9).…”
Section: Pkcmentioning
confidence: 99%